The potential immunomodulatory effect of levamisole in humans and farm animals - Gholami, Mohammad Hossein; Rassouli, Ali; Mirzaei, Sepideh; Hashemi, Farid (Journal of Advanced Veterinary and Animal Research, 2023)
This study conducted a literature review to investigate the immunomodulatory effect of levamisole in both humans and farm animals. The following procedure was followed for database searching: PubMed, Google Scholar, Web of Science, and Cochrane Library. All research works were updated to September 2022. The terms used in the literature search were included: (“levamisole” OR “immunity” OR “immune system”) AND (“adjuvant” OR “fish” OR “poultry” OR “farm animal” OR “cattle” OR “sheep”). The current review enlightens the extensive potential of levamisole as an adjuvant immunotherapeutic agent and explains its divergent applications beyond its antiparasitic use as an adjuvant, dietary supplement, immunostimulant, antiviral, and anti-cancer drug in humans and farm animals. In the articles examined, various mechanisms have been proposed for levamisole immunoprotective effects, but hormonal alteration and stress hormone reduction are indicated as the main mechanisms in various animal species. J. Adv. Vet. Anim. Res., 10(4): 620–629, December 2023 http://doi.org/10.5455/javar.2023.j717